2018
DOI: 10.3904/kjim.2018.289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of anti-thyroglobulin antibody measurement before surgery in thyroid cancer

Abstract: Thyroglobulin antibody (TgAb) is a class G immunoglobulin and a conventional marker for thyroid autoimmunity. From a clinical perspective, TgAb is less useful than thyroid peroxidase antibodies for predicting thyroid dysfunction. However, TgAb is found more frequently in differentiated thyroid cancer (DTC) and can interfere with thyroglobulin (Tg) measurements, which are used to monitor the recurrence or persistence of DTC. Recent studies suggested a small but consistent role for preoperative TgAb in predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…Previous studies have indicated that TgAb and Tg are important biomarkers for the diagnosis of DTC ( 15 , 16 ). The diagnostic efficiency of exosomal miR-130a-3p was then compared with that of TgAb and Tg in patients with DTC and benign thyroid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that TgAb and Tg are important biomarkers for the diagnosis of DTC ( 15 , 16 ). The diagnostic efficiency of exosomal miR-130a-3p was then compared with that of TgAb and Tg in patients with DTC and benign thyroid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no significant difference in the subjects who had anti-Tg earlier than the control group. This is expected, since anti-Tg is a well-established marker in differentiated thyroid cancer (DTC) diagnosis and is considered a less specific marker in thyroid disease compared to anti-TPO [23]. Even though our study was limited to 2 years, our results correlate with a study performed by Hutfless et al that showed the preexistence of anti-TPO and anti-Tg autoantibodies 7 years prior to the concise diagnosis of Hashimoto's (66% and 57% for anti-TPO and anti-Tg, respectively) and Graves' disease (57% and 47% for anti-TPO and anti-Tg, respectively) for 174 patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…• THW: This consists of L-T4 deprivation for 3 to 4 wk or triiodothyronine (T3) treatment for 4 wk with subsequent T3 discontinuation for 2 wk before RAI scintigraphy. • rhTSH stimulation: This consists of administration of rhTSH given as 2 intramuscular injections of 0.9 mg on each of 2 consecutive days with RAI or 18 F-FDG given the next day. rhTSH may be required if the patient cannot be prepared by near-total thyroidectomy, in patients with significant comorbidities in whom prolonged hypothyroidism would represent a risk or cannot be tolerated, in patients with pituitary insufficiency, or in those with isolated TSH deficiency.…”
Section: B Patient Preparationmentioning
confidence: 99%
“…The typical administered dosage for oncology is 370-740 MBq (10-20 mCi). 18 F-FDG may be used to identify tumors that are not detected with RAI. These are usually less well-differentiated tumors ( 18 F-FDG-positive, radioiodine-negative) and are less likely to respond to 131 I-NaI treatment.…”
Section: Radiopharmaceuticals and Dosagementioning
confidence: 99%
See 1 more Smart Citation